An Elastoplastic Softening Damage Model for Hydraulic Fracturing in Soft Coal Seams - Yang Hao; Yu Wu; Xianbiao Mao; Pan Li; Liqiang Zhang; Jing Tao (Advances in Civil Engineering)
In order to improve the permeability of soft coal seams with low intensity and permeability by hydraulic fracturing, an elastoplastic softening damage model of soft coal seams has been established, which takes into consideration the lower elastic modulus and tensile strength and higher pore compressibility and plastic deformation. The model then was implemented to FLAC3D finite difference software to be verified with the on-site results of the Number 2709 coalface in Datong coal mine, China. The modelling results of fracture-influenced radius show good consistency with on-site results. Then the parameters of water injection rate and time on fracture-influenced radius were studied. The results indicate that the fracture-influenced radius increases rapidly with an increased injection rate initially. After reaching the maximum value, fracture-influenced radius decreases slowly with further increase of the injection rate. Finally, it remains constant. The fracture-influenced radius rapidly increases initially at a certain time and then slowly increases with the injection time. The novel model and numerical method could be used to predict the radius of hydraulic fracture-influenced area and choose the suitable injection parameters to help the on-site work more efficiently.